Ferrite magnetic tile and preparation method thereof

Through the injection molding and sintering process of ferrite magnetic powder and binder, the problems of low performance and complex processing of large-arc ultra-thin magnetic tiles in traditional processes are solved, and the preparation of high-performance magnetic tiles is realized, with excellent magnetic properties and high yield.

CN119495484APending Publication Date: 2025-02-21HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311028861.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

It is difficult to effectively prepare high-performance large-arc ultra-thin ferrite magnetic tiles with high performance. Traditional processes have problems such as many grinding times, low material utilization, and low mechanical strength of magnetic tiles.

Method used

The mixture of ferrite magnetic powder and binder is used for injection molding and sintering, with a sintering temperature of 1150-1240℃, and surface modification and optimized ratio of binder before sintering, including paraffin and stearic acid wax , polyethylene and other components.

Benefits of technology

The prepared magnetic tiles exhibit excellent magnetic properties, with a central surface magnet of 630~700Gs, a magnetic energy product of 4.5~5.2MGOe, a density of 4.8~5.2g/cm3, a compressive strength of 480~680N, and a dark crack inside. Fewer, no post-grinding processing is required, the yield and material utilization rate are high, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495484A_ABST
    Figure CN119495484A_ABST
Patent Text Reader

Abstract

The invention provides a ferrite magnetic tile and a preparation method thereof, and the preparation method comprises the following steps: carrying out injection molding on a mixed material of ferrite magnetic powder and a binder, and sintering to obtain the ferrite magnetic tile, the sintering temperature ranges from 1150 DEG C to 1240 DEG C. The large-radian ultra-thin magnetic shoe obtained through the preparation method shows excellent magnetic performance, the center surface magnetism ranges from 630 Gs to 700 Gs, the magnetic energy product can reach 4.5 MGOe to 5.2 MGOe, the density ranges from 4.8 g / cm < 3 > to 5.2 g / cm < 3 >, and the compressive strength ranges from 480 N to 680 N and is obviously higher than that of an existing injection molding permanent magnetic ferrite magnet; according to the large-radian ultra-thin magnetic shoe obtained through the preparation method, the internal dark cracks are few, meanwhile, later grinding machining is basically not needed, the risk of stress damage generated in the machining process is reduced, the yield and the utilization rate of materials are increased, the yield is not lower than 95%, the utilization rate of the materials is not lower than 90%, and the large-radian ultra-thin magnetic shoe is suitable for large-radian ultra-thin magnetic shoes. Therefore, the production cost is reduced, and the requirement of batch production is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent magnets, and relates to a method for preparing a ferrite magnetic tile, in particular to a ferrite magnetic tile and a method for preparing the same. Background Art

[0002] Permanent magnetic materials are materials that can maintain constant magnetism once magnetized, also known as hard magnetic materials. Commonly used permanent magnetic materials include aluminum nickel cobalt permanent magnet alloys, ferrite permanent magnets, rare earth permanent magnets and various composite permanent magnetic materials. Permanent ferrite is one of the basic functional materials of permanent magnet DC motors. It can meet the use requirements of motors in various environments. It has high sensitivity and stability and can be widely used in various types of high-power, high-speed, and high-torque motors, such as high-end automotive motors (ABS motors, starter motors, etc.), motorcycle starter motors, household appliances, and power tool motors. In order to facilitate the production of motor stators or rotors, permanent ferrites used in motors are mostly made into tile-shaped, referred to as magnetic tiles. The size parameters of permanent ferrite magnetic tiles mainly include chord length, width, inner and outer arc radius, thickness, and the arc corresponding to the chord length.

[0003] Traditional permanent ferrite tiles are mainly prepared by wet-molding magnetic field forming process, which specifically includes: wet-milling the ferrite coarse powder to an average particle size of less than 1.0 μm, and then concentrating and dehydrating to obtain a ferrite slurry with a solid content of about 65wt% and good fluidity, and then assembling a tile-shaped mold through a hydraulic press under magnetic field conditions to complete the molding to obtain a ferrite blank; further using a sintering furnace to sinter the blank at high temperature to obtain a semi-finished tile; then using a grinder to grind the inner and outer arcs, chord length, width and chamfers to obtain a product that meets the size requirements of the drawing. The wet-molding tile preparation process has the advantages of high production efficiency, stable and reliable performance, and controllable dimensional accuracy. It is currently the most mainstream method for preparing permanent ferrite tiles. However, the tiles prepared by this process have many grinding machine processing times, large grinding volume, and relatively low material utilization; at the same time, the repeated grinding process is prone to produce internal stress in the tiles, resulting in low mechanical strength of the tiles. Especially for large-arc ultra-thin magnetic tiles (arc greater than 150°, thickness less than 2.0mm), the disadvantages of traditional production processes will be more obvious, the grinding volume will account for a larger proportion, the material utilization rate will be lower, and defects such as corner chipping and cracking during the grinding process of the magnetic tiles will result in a lower yield rate, and the mechanical strength of the product will be so low that it cannot be used at all.

[0004] Ferrite magnetic tiles can also be prepared by injection molding. The main process includes: mixing and granulating magnetic powder of a certain particle size and resin powder; then injecting the granulated granules into the injection molding machine and heating and melting them to make them have good fluidity. In this state, the granules are injected into a tile-shaped metal mold with an oriented magnetic field in a molten state, and after cooling, the required tile-shaped injection-molded ferrite device is formed. Traditional injection-molded tile-shaped ferrite has the advantages of net size molding, no need for grinding, high material utilization, and good mechanical strength. It is particularly suitable for processing large-arc ultra-thin magnetic tiles, but the process has low magnetic properties, and the maximum magnetic energy product does not exceed 2.5MGOe, which is difficult to meet the needs of related application scenarios.

[0005] CN102136332A discloses a flexible permanent magnetic ferrite material for injection molding and a manufacturing method thereof, belonging to the field of permanent magnetic ferrite materials. The granular material is compounded by 80-92% of permanent magnetic ferrite, 3-6% of rubber, 2.5-10% of plasticizer and 0.1-3% of auxiliary agent in terms of mass percentage; wherein the permanent magnetic ferrite is strontium ferrite Sr 0.6 Fe2O3; The rubber includes main rubber and auxiliary rubber, and the main rubber content accounts for 55-95% of the total rubber mass. 0.6 Fe2O3 as a permanent ferrite is compounded with rubber, plasticizer and additives to form a flexible permanent ferrite material. The material can be made into flexible injection pellets, which can be injection molded into position sensors. The manufactured position sensors are flexible sensors with good flexibility, which are different from the rigid position sensors with poor flexibility made of traditional nylon injection pellets, making the position sensors more durable, convenient and low-cost.

[0006] CN102351525A discloses a method for manufacturing permanent magnet ferrite powder for injection molding, comprising the following process steps: first, uniformly mixing raw materials consisting of iron oxide, A carbonate, densifier, and sintering aid, wherein A is one or a mixture of two of Sr, Ba, Pb, and Ca; second, dry-firing the mixed raw materials; then, grinding the fired materials; and finally, heat treating. The method for manufacturing permanent magnet ferrite powder for injection molding of the invention does not require a molding process due to the addition of a densifier, but directly sintering the mixed dry powder, and after direct dry sintering, it can be directly washed with water and ground into fine powder without going through a crushing and / or coarse grinding process, the process is simple, and permanent magnet ferrite powder with ideal grain morphology, good filling property, high magnetic force and uniformity can be obtained.

[0007] The currently disclosed ferrite magnetic tiles and their preparation methods have certain defects, and there is a problem that it is difficult to effectively prepare high-performance large-radian ultra-thin magnetic tiles. Therefore, it is very important to develop and design a new type of ferrite magnetic tile and its preparation method. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a ferrite magnetic tile and a preparation method thereof. The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention exhibits excellent magnetic properties, with a central surface magnetism of 630-700Gs, a magnetic energy product of 4.5-5.2MGOe, and a density of 4.8-5.2g / cm 3 The compressive strength is 480-680N, which is significantly higher than that of the existing injection molded permanent ferrite magnets. The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention has fewer internal dark cracks and basically does not require subsequent grinding processing, which not only reduces the risk of stress damage during processing, but also improves the yield and utilization rate of the material. The yield rate is not less than 95%, and the material utilization rate is not less than 90%, thereby reducing the production cost and meeting the requirements of mass production.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising:

[0011] The mixture of ferrite magnetic powder and binder is injection molded and then sintered to obtain ferrite magnetic tiles;

[0012] The sintering temperature is 1150-1240°C.

[0013] The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention exhibits excellent magnetic properties, with a central surface magnetism of 630-700Gs, a magnetic energy product of 4.5-5.2MGOe, and a density of 4.8-5.2g / cm 3 The compressive strength is 480-680N, which is significantly higher than that of the existing injection molded permanent ferrite magnets. The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention has fewer internal dark cracks and basically does not require subsequent grinding processing, which not only reduces the risk of stress damage during processing, but also improves the yield and utilization rate of the material. The yield rate is not less than 95%, and the material utilization rate is not less than 90%, thereby reducing the production cost and meeting the requirements of mass production.

[0014] The sintering temperature in the present invention is 1150-1240°C, for example, it can be 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, 1210°C, 1220°C, 1230°C or 1240°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the mixture further comprises a surface modifier, a coupling agent and a flow aid.

[0016] The surface modifier in the present invention is used to quickly remove fine magnetic powder and spheroidize the edges and corners of the magnetic powder, thereby improving the fluidity of the magnetic powder.

[0017] Preferably, based on the mass of the mixed material, the mass fraction of ferrite powder is 88.3-94.3wt%, the mass fraction of surface modifier is 0.1-0.9wt%, the mass fraction of coupling agent is 0.3-1.0wt%, the mass fraction of binder is 5-9wt%, and the mass fraction of flow aid is 0.3-0.8wt%.

[0018] In the present invention, taking the mass of the mixed material as 100%, the mass fraction of the ferrite powder is 88.3-94.3wt%, for example, it can be 88.3wt%, 88.5wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt% or 94.3wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, the mass fraction of the surface modifier is 0.1-0.9wt%, based on the mass of the mixed material as 100%, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or 0.9wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In the present invention, based on the mass of the mixed material as 100%, the mass fraction of the coupling agent is 0.3-1.0wt%, for example, it can be 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% or 1wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In the present invention, the mass fraction of the binder is 5 to 9wt% based on the mass of the mixed material, for example, it can be 5wt%, 6wt%, 7wt%, 8wt% or 9wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In the present invention, the mass fraction of the flow aid is 0.3-0.8wt% based on the mass of the mixed material. For example, it can be 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt% or 0.9wt%, but it is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the surface modifier includes any one of phosphoric acid, oxalic acid, acetic acid, and citric acid, or a combination of at least two of them. Typical but non-limiting combinations include a combination of phosphoric acid and oxalic acid, a combination of oxalic acid and acetic acid, a combination of acetic acid and citric acid, or a combination of phosphoric acid, oxalic acid, and acetic acid.

[0024] Preferably, the concentration of the surface modifier is 10-20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the coupling agent comprises stearic acid and / or an ester derivative of stearic acid.

[0026] Preferably, the ester derivatives of stearic acid include butyl stearate and / or octyl stearate.

[0027] Preferably, the flow aid comprises polyamide wax.

[0028] Preferably, the binder includes: paraffin and / or microcrystalline wax, stearic acid wax, high-density polyethylene and low-density polyethylene. The binder is used to ensure that the embryo obtained by subsequent injection molding maintains a certain strength, thereby preventing the blank from deforming during sintering.

[0029] The paraffin wax described in the present invention is a solid crystalline product extracted from petroleum, which is composed of various hydrocarbons, mainly normal alkanes, and also contains isoalkanes, cycloalkanes and a small amount of aromatic hydrocarbons; the paraffin wax described in the present invention includes but is not limited to 60# paraffin wax, and other paraffin waxes not listed are also applicable.

[0030] The paraffin in the binder of the present invention has two functions. The first is to act as an organic binder to achieve the bonding of ferrite magnetic powder, and the second is to increase the fluidity of ferrite magnetic powder. When the content of paraffin in the binder is too low, the fluidity of the mixture of ferrite magnetic powder and the binder will be poor, so that normal injection molding cannot be performed; when the content of paraffin in the binder is too high, the pores of the product after the paraffin is removed will be too large, so that the strength will be reduced, and the volume change will be too large during sintering, so that cracks will occur.

[0031] In the present invention, microcrystalline wax can be used to replace paraffin wax to obtain better product performance. The microcrystalline wax is also called ozokerite. The main components of microcrystalline wax are cycloalkanes and aromatic hydrocarbons with larger molecular weight and longer carbon chains. Under a microscope, it can be clearly seen that its crystals are much smaller than those of paraffin wax.

[0032] Preferably, based on the mass of the binder, the mass fraction of paraffin and / or microcrystalline wax is 50-70wt%, the mass fraction of stearic acid wax is 10-20wt%, the mass fraction of high-density polyethylene is 10-15wt%, and the mass fraction of low-density polyethylene is 10-15wt%.

[0033] In the present invention, taking the mass of the binder as 100%, the mass fraction of paraffin wax and / or microcrystalline wax is 50-70wt%, for example, it can be 50wt%, 52wt%, 54wt%, 56wt%, 58wt%, 60wt%, 62wt%, 64wt%, 66wt%, 68wt% or 70wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, taking the mass of the binder as 100%, the mass fraction of stearic acid wax is 10-20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In the present invention, taking the mass of the binder as 100%, the mass fraction of high-density polyethylene is 10-15wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In the present invention, taking the mass of the binder as 100%, the mass fraction of the low-density polyethylene is 10-15wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the method for preparing the mixed material comprises: finely grinding ferrite magnetic powder, a surface modifier, a coupling agent and a binder to obtain a mixed material.

[0038] Preferably, the mixing includes: mixing the ferrite powder and the surface modifier at a first temperature to obtain a first mixed powder, then adding a coupling agent for a second temperature mixing to obtain a second mixed powder, and further adding a flow aid and a binder for a third temperature mixing to obtain a mixed material.

[0039] Preferably, the first heating and mixing comprises: taking ferrite magnetic powder, heating it to 80-120° C. while stirring, then adding a surface modifier, and continuing to stir for 5-15 minutes to obtain a first mixed powder;

[0040] The terminal temperature of the first heating and mixing in the present invention is 80-120°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The stirring time in the first heating mixing of the present invention is 5 to 15 minutes, for example, it can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the second temperature-raising mixing comprises: heating the first mixed powder to 90-130° C. while stirring, then adding a coupling agent, and continuing stirring for 20-40 minutes to obtain a second mixed powder;

[0043] The terminal temperature of the second heating and mixing in the present invention is 90-130°C, for example, it can be 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] The stirring time in the second heating mixing described in the present invention is 20 to 40 minutes, for example, it can be 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the third heating and mixing method includes: adjusting the temperature of the second mixed powder to 80-100° C., then adding a flow aid and a binder, and continuing to mix for 20-40 minutes to obtain a final mixed material;

[0046] The third heating and mixing adjustment temperature of the present invention is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] The time for the third heating and mixing of the present invention is 20 to 40 minutes, for example, it can be 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] Preferably, the moisture content of the first mixing powder is not higher than 600 ppm, for example, it may be 600 ppm, 550 ppm, 500 ppm, 450 ppm, 400 ppm, 350 ppm, 300 ppm, 250 ppm, 200 ppm, 150 ppm or 100 ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the moisture content of the second mixing powder is not higher than 900 ppm, for example, it may be 900 ppm, 800 ppm, 700 ppm, 600 ppm, 500 ppm, 400 ppm, 300 ppm, 200 ppm or 100 ppm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the method for preparing the ferrite magnetic powder comprises: mixing additives into permanent magnet ferrite coarse powder, and then wet-milling the mixture, and drying the mixture to obtain ferrite finely ground magnetic powder having an average particle size of 0.8 to 1.2 μm.

[0051] Preferably, the chemical formula of the permanent ferrite coarse powder includes A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or any one or a combination of at least two of Sr and Ba, 0.25≤x≤0.45, 0.35≤y≤0.55, 0.25≤z≤0.40, 0.6≤z / y≤0.9 and 5.1≤n≤5.6.

[0052] In the present invention, 0.25≤x≤0.45, and x can be, for example, 0.25, 0.27, 0.3, 0.32, 0.35, 0.37, 0.4, 0.42 or 0.45, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In the present invention, 0.35≤y≤0.55, and y can be, for example, 0.35, 0.37, 0.4, 0.42, 0.45, 0.47, 0.5, 0.52 or 0.35, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In the present invention, 0.25≤z≤0.40, z can be, for example, 0.25, 0.27, 0.3, 0.32, 0.35, 0.37 or 0.4, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In the present invention, 0.6≤z / y≤0.9, and z / y can be, for example, 0.6, 0.65, 0.7, 0.75, 0.8, 0.86 or 0.9, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In the present invention, 5.1≤n≤5.6, and n can be, for example, 5.1, 5.2, 5.3, 5.4, 5.5 or 5.6, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0057] Preferably, the additives include SiO2, CaCO3 and H3BO3.

[0058] Preferably, the additives also include Al2O3, Cr2O3, ZnO and SrCO3.

[0059] Preferably, the average particle size of the additive is not higher than 5 μm, for example, it can be 5 μm, 4.5 μm, 3 μm, 2.5 μm, 2 μm, 1.5 μm or 1 μm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] Preferably, based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.05-2.0wt%, the mass fraction of CaCO3 is 0.4-2.0wt%, the mass fraction of Al2O3 is 0.1-2.0wt%, the mass fraction of Cr2O3 is 0.1-1.5wt%, the mass fraction of ZnO is 0.1-0.6wt%, the mass fraction of SrCO3 is 0.1-1.0wt%, and the mass fraction of H3BO3 is 0.1-0.8wt%.

[0061] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of SiO2 is 0.05-2.0wt%, for example, it can be 0.05wt%, 0.07wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of CaCO3 is 0.4-2.0wt%, for example, it can be 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0063] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of Al2O3 is 0.1-2.0wt%, for example, it can be 0.1wt%, 0.2wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of Cr2O3 is 0.1-1.5wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt% or 1.5wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of ZnO is 0.1-0.6wt%, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or 0.6wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of SrCO3 is 0.1-1.0wt%, for example, it can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt% or 1wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In the present invention, taking the total mass of the permanent magnet ferrite coarse powder and the additives as 100%, the mass fraction of H3BO3 is 0.1-0.8wt%, for example, it can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt% or 0.8wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the preparation method further comprises mixing and granulation performed sequentially before the injection molding.

[0069] Preferably, the mixing temperature is 100-150° C. and the mixing time is 1-3 hours.

[0070] The mixing temperature in the present invention is 100-150°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] The mixing time in the present invention is 1 to 3 hours, for example, it can be 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.4 hours, 2.6 hours, 2.8 hours or 3 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] Preferably, the average particle size of the mixed material obtained after granulation is 6 to 8 mm, for example, it can be 6 mm, 6.2 mm, 6.4 mm, 6.6 mm, 6.8 mm, 7 mm, 7.2 mm, 7.4 mm, 7.6 mm, 7.8 mm or 8 mm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] Preferably, the injection molding temperature is 100-150°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] Preferably, the injection molding pressure is 75 to 200 bar, for example, it can be 75 bar, 80 bar, 90 bar, 100 bar, 110 bar, 120 bar, 130 bar, 140 bar, 150 bar, 160 bar, 170 bar, 180 bar, 190 bar or 200 bar, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] Preferably, the injection molding is performed in a shoe-shaped molding cavity with a magnetic field.

[0076] Preferably, natural cooling is further included between the injection molding and the sintering.

[0077] Preferably, the preparation method further comprises debinding between the injection molding and the sintering.

[0078] Preferably, the degreasing comprises solvent degreasing and thermal degreasing performed sequentially.

[0079] Preferably, the solvent degreasing comprises: immersing the embryo body obtained by injection molding in kerosene.

[0080] In the present invention, most of the paraffin is firstly removed by long-term immersion in kerosene, thereby avoiding excessive and uneven pores caused by the volatilization of the paraffin during sintering, thereby improving the strength of the product. The obtained product has uniform pores and high density, and the density of the embryo body after degreasing is high.

[0081] In the thermal degreasing step of the present invention, by adopting a process of slowly heating up from a low temperature, the organic binder other than the paraffin is slowly melted and gradually seeps out of the surface of the embryo obtained by injection molding, thereby avoiding the gasification of these organic substances in the subsequent sintering process to generate a large number of irregular pores, thereby improving the strength of the manufactured product, ensuring the density of the product, and ultimately obtaining a high-density ferrite tile.

[0082] Preferably, the soaking temperature is 40-60° C. and the soaking time is 5-8 hours.

[0083] The immersion temperature in the present invention is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] The soaking time in the present invention is 5 to 8 hours, for example, it can be 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] Preferably, the thermal degreasing comprises sequentially heating and heat preservation;

[0086] Preferably, the heating rate is 10-15°C / min, and the terminal temperature is 400-800°C.

[0087] The heating rate described in the present invention is 10 to 15°C / min, for example, it can be 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min or 15°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] The terminal temperature of the heating in the present invention is 400-800°C, for example, 400°C, 500°C, 600°C, 700°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] Preferably, the insulation time is 4 to 6 hours, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5h, 5.2h, 5.4h, 5.6h, 5.8h or 6h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] Preferably, the sintering time is 2 to 6 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0091] The sintering is performed in an air atmosphere.

[0092] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:

[0093] (1) Additives having an average particle size of no more than 5 μm are mixed into coarse permanent ferrite powder having an average particle size of 4 to 6 μm, and then wet-milled to obtain ferrite powder having an average particle size of 0.8 to 1.2 μm after drying;

[0094] The chemical formula of the permanent ferrite coarse powder includes A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or any one or a combination of at least two of Sr and Ba, 0.25≤x≤0.45, 0.35≤y≤0.55, 0.25≤z≤0.40, 0.6≤z / y≤0.9 and 5.1≤n≤5.6;

[0095] Taking the total mass of the permanent magnet ferrite coarse powder and the additive as 100%, the mass fraction of SiO2 is 0.05-2.0wt%, the mass fraction of CaCO3 is 0.4-2.0wt%, the mass fraction of Al2O3 is 0-2.0wt%, the mass fraction of Cr2O3 is 0-1.5wt%, the mass fraction of ZnO is 0-0.6wt%, the mass fraction of SrCO3 is 0.1-1.0wt%, and the mass fraction of H3BO3 is 0-0.8wt%;

[0096] (2) taking the ferrite powder obtained in step (1), heating it to 80-120° C. while stirring, then adding a surface modifier, and continuing to stir for 5-15 minutes to obtain a first mixed powder; heating the first mixed powder to 90-130° C. while stirring, then adding a coupling agent, and continuing to stir for 20-40 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 80-100° C., then adding a flow aid and a binder, and continuing to mix for 20-40 minutes to obtain a final mixed material;

[0097] Based on the mass of the mixed material, the mass fraction of the ferrite powder is 88.3-94.3wt%, the mass fraction of the surface modifier is 0.1-0.9wt%, the mass fraction of the coupling agent is 0.3-1.0wt%, the mass fraction of the binder is 5-9wt%, and the mass fraction of the flow aid is 0.3-0.8wt%;

[0098] Based on the mass of the binder, the mass fraction of paraffin wax and / or microcrystalline wax is 50-70wt%, the mass fraction of stearic acid wax is 10-20wt%, the mass fraction of high-density polyethylene is 10-15wt%, and the mass fraction of low-density polyethylene is 10-15wt%;

[0099] (3) kneading the mixture obtained in step (2) at 100-150° C. for 1-3 hours, and granulating to obtain permanent magnet ferrite particles with an average particle size of 6-8 mm;

[0100] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 100 to 150° C. and a pressure of 75 to 200 bar, and obtaining an embryo after natural cooling;

[0101] (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 40 to 60° C. for 5 to 8 hours for solvent degreasing, then heating to 400 to 800° C. at a rate of 10 to 15° C. / min and keeping the temperature for 4 to 6 hours for thermal degreasing to obtain a degreased embryo;

[0102] (6) Sintering the degreased embryo obtained in step (5) at 1150-1240° C. for 2-6 hours in an air atmosphere to obtain a ferrite tile.

[0103] In a second aspect, the present invention provides a ferrite magnetic tile, wherein the ferrite magnetic tile is obtained by the preparation method described in the first aspect.

[0104] Preferably, the ferrite magnetic tile has an arc greater than 150° and a thickness not greater than 2.0 mm.

[0105] The curvature of the ferrite magnetic tile described in the present invention is greater than 150°, for example, it can be 151°, 155°, 156°, 157°, 158°, 159°, 160°, 161°, 162°, 163°, 164°, 165°, 167°, 168°, 170°, 172° or 175°, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0106] The thickness of the ferrite magnetic tile described in the present invention is not higher than 2.0 mm, for example, it can be 2.0 mm, 1.9 mm, 1.8 mm, 1.6 mm, 1.4 mm, 1.2 mm or 1.0 mm, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0107] Preferably, the magnetic energy product of the ferrite magnetic tile is 4.5-5.2MGOe, for example, 4.5MGOe, 4.6MGOe, 4.7MGOe, 4.8MGOe, 4.9MGOe, 5MGOe, 5.1MGOe or 5.2MGOe, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0108] Compared with the prior art, the present invention has the following beneficial effects:

[0109] The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention exhibits excellent magnetic properties, with a central surface magnetism of 630-700Gs, a magnetic energy product of 4.5-5.2MGOe, and a density of 4.8-5.2g / cm 3 The compressive strength is 480-680N, which is significantly higher than that of the existing injection molded permanent ferrite magnets. The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention has fewer internal dark cracks and basically does not require subsequent grinding processing, which not only reduces the risk of stress damage during processing, but also improves the yield and utilization rate of the material. The yield rate is not less than 95%, and the material utilization rate is not less than 90%, thereby reducing the production cost and meeting the requirements of mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0110] Figure 1 This is a schematic diagram of the structure of the ferrite magnetic tile prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0111] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0112] Example 1

[0113] The present invention provides a Figure 1 The preparation method of the ferrite magnetic tile shown in the figure comprises:

[0114] (1) mixing an additive having an average particle size of 3 μm into a permanent ferrite coarse powder having an average particle size of 5 μm, and then wet-milling the mixture, and drying the mixture to obtain a ferrite magnetic powder having an average particle size of 0.9 μm;

[0115] The chemical formula of the permanent ferrite coarse powder includes Sr 0.25 Ca 0.3 La 0.45 Fe 11.3 Co 0.32 O 19 , the additives are SiO2, CaCO3 and H3BO3, and based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.5wt%, the mass fraction of CaCO3 is 1.5wt%, and the mass fraction of H3BO3 is 0.4wt%;

[0116] (2) taking the ferrite powder obtained in step (1), heating it to 85° C. while stirring, then adding 15% phosphoric acid, and continuing to stir for 10 minutes to obtain a first mixed powder; heating the first mixed powder to 100° C. while stirring, then adding stearic acid, and continuing to stir for 30 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 90° C., then adding polyamide wax and a binder, and continuing to mix for 20 minutes to obtain a final mixed material;

[0117] Based on the mass of the mixed material, the mass fraction of the ferrite magnetic powder is 93wt%, the mass fraction of 15% phosphoric acid is 0.5wt%, the mass fraction of stearic acid is 0.5wt%, the mass fraction of the binder is 5.6wt%, and the mass fraction of the polyamide wax is 0.4wt%;

[0118] Taking the mass of the binder as 100%, the mass fraction of paraffin in the binder is 60wt%, the mass fraction of stearic acid wax is 10wt%, the mass fraction of high-density polyethylene is 15wt%, and the mass fraction of low-density polyethylene is 15wt%;

[0119] (3) kneading the mixture obtained in step (2) at 120° C. for 2 h, and granulating to obtain permanent magnet ferrite particles with an average particle size of 7 mm;

[0120] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 140° C. and a pressure of 180 bar, and obtaining an embryo after natural cooling;

[0121] (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 50° C. for 8 h for solvent degreasing, then heating to 700° C. at a rate of 12° C. / min and keeping the temperature for 6 h for thermal degreasing to obtain a degreased embryo;

[0122] (6) Sinter the degreased embryo obtained in step (5) at 1240° C. for 5 h in an air atmosphere to obtain a ferrite tile.

[0123] Example 2

[0124] The present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising:

[0125] (1) mixing an additive having an average particle size of 2 μm into a permanent ferrite coarse powder having an average particle size of 4 μm, and then wet-milling the mixture, and drying the mixture to obtain a ferrite magnetic powder having an average particle size of 0.8 μm;

[0126] The chemical formula of the permanent ferrite coarse powder includes Sr 0.20 Ca 0.28 La 0.52 Fe 11.4 Co 0.30 O 19 , the additives are SiO2, CaCO3, H3BO3, ZnO and Al2O3, based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.6wt%, the mass fraction of CaCO3 is 1.3wt%, the mass fraction of H3BO3 is 0.3wt%, the mass fraction of ZnO is 0.2wt% and the mass fraction of Al2O3 is 0.4wt%;

[0127] (2) taking the ferrite powder obtained in step (1), heating it to 85° C. while stirring, then adding 15% citric acid, and continuing to stir for 10 minutes to obtain a first mixed powder; heating the first mixed powder to 100° C. while stirring, then adding butyl stearate, and continuing to stir for 30 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 90° C., then adding polyamide wax and a binder, and continuing to mix for 20 minutes to obtain a final mixed material;

[0128] Based on the mass of the mixed material, the mass fraction of the ferrite magnetic powder is 91wt%, the mass fraction of 15% citric acid is 0.8wt%, the mass fraction of butyl stearate is 0.4wt%, the mass fraction of the binder is 7.3wt%, and the mass fraction of the polyamide wax is 0.5wt%;

[0129] Taking the mass of the binder as 100%, the mass fraction of paraffin in the binder is 60wt%, the mass fraction of stearic acid wax is 15wt%, the mass fraction of high-density polyethylene is 10wt%, and the mass fraction of low-density polyethylene is 10wt%;

[0130] (3) kneading the mixture obtained in step (2) at 120° C. for 2 h, and granulating to obtain permanent magnet ferrite particles with an average particle size of 7 mm;

[0131] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 140° C. and a pressure of 180 bar, and obtaining an embryo after natural cooling;

[0132] (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 50° C. for 8 h for solvent degreasing, then heating to 800° C. at a rate of 12° C. / min and keeping the temperature for 6 h for thermal degreasing to obtain a degreased embryo;

[0133] (6) Sinter the degreased embryo obtained in step (5) at 1240° C. for 6 h in an air atmosphere to obtain a ferrite tile.

[0134] Example 3

[0135] The present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising:

[0136] (1) mixing an additive having an average particle size of 5 μm into a coarse permanent ferrite powder having an average particle size of 6 μm, and then wet-milling the mixture, and drying the mixture to obtain ferrite powder having an average particle size of 1.2 μm;

[0137] The chemical formula of the permanent ferrite coarse powder includes Sr 0.15 Ca 0.35 La 0.50 Fe 11.4 Co 0.26 O 19 ,, the additives are SiO2, CaCO3, H3BO3 and Cr2O3, and based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.4wt%, the mass fraction of CaCO3 is 1.8wt%, the mass fraction of H3BO3 is 0.2wt% and the mass fraction of Cr2O3 is 0.1wt%;

[0138] (2) taking the ferrite powder obtained in step (1), heating it to 85° C. while stirring, then adding 15% acetic acid, and continuing to stir for 10 minutes to obtain a first mixed powder; heating the first mixed powder to 100° C. while stirring, then adding octyl stearate, and continuing to stir for 30 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 90° C., then adding polyamide wax and a binder, and continuing to mix for 20 minutes to obtain a final mixed material;

[0139] Based on the mass of the mixed material, the mass fraction of the ferrite magnetic powder is 94wt%, the mass fraction of 15% acetic acid is 0.4wt%, the mass fraction of octyl stearate is 0.3wt%, the mass fraction of the binder is 5wt%, and the mass fraction of the polyamide wax is 0.3wt%;

[0140] Taking the mass of the binder as 100%, the mass fraction of paraffin in the binder is 55wt%, the mass fraction of stearic acid wax is 15wt%, the mass fraction of high-density polyethylene is 15wt%, and the mass fraction of low-density polyethylene is 15wt%;

[0141] (3) kneading the mixture obtained in step (2) at 120° C. for 2 h, and granulating to obtain permanent magnet ferrite particles with an average particle size of 7 mm;

[0142] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 140° C. and a pressure of 180 bar, and obtaining an embryo after natural cooling;

[0143] (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 50° C. for 8 h for solvent degreasing, then heating to 800° C. at a rate of 12° C. / min and keeping the temperature for 6 h for thermal degreasing to obtain a degreased embryo;

[0144] (6) Sinter the degreased embryo obtained in step (5) at 1240° C. for 6 h in an air atmosphere to obtain a ferrite tile.

[0145] Example 4

[0146] The present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising:

[0147] (1) mixing an additive having an average particle size of 1 μm into a coarse permanent ferrite powder having an average particle size of 5 μm, and then wet-milling the mixture, and drying the mixture to obtain a ferrite powder having an average particle size of 0.9 μm;

[0148] The chemical formula of the permanent ferrite coarse powder includes Sr 0.25 Ca 0.3 La 0.45 Fe11.3 Co 0.32 O 19 , the additives are SiO2, CaCO3 and H3BO3, and based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.5wt%, the mass fraction of CaCO3 is 1.5wt%, and the mass fraction of H3BO3 is 0.4wt%;

[0149] (2) taking the ferrite powder obtained in step (1), heating it to 80° C. while stirring, then adding 15% phosphoric acid, and continuing to stir for 15 minutes to obtain a first mixed powder; heating the first mixed powder to 90° C. while stirring, then adding stearic acid, and continuing to stir for 40 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 80° C., then adding polyamide wax and a binder, and continuing to mix for 40 minutes to obtain a final mixed material;

[0150] Based on the mass of the mixed material, the mass fraction of the ferrite magnetic powder is 93wt%, the mass fraction of 15% phosphoric acid is 0.5wt%, the mass fraction of stearic acid is 0.5wt%, the mass fraction of the binder is 5.6wt%, and the mass fraction of the polyamide wax is 0.4wt%;

[0151] Taking the mass of the binder as 100%, the mass fraction of paraffin in the binder is 60wt%, the mass fraction of stearic acid wax is 10wt%, the mass fraction of high-density polyethylene is 15wt%, and the mass fraction of low-density polyethylene is 15wt%;

[0152] (3) kneading the mixture obtained in step (2) at 100° C. for 3 h, and granulating to obtain permanent magnet ferrite particles with an average particle size of 8 mm;

[0153] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 100° C. and a pressure of 200 bar, and obtaining an embryo after natural cooling;

[0154] (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 40° C. for 7 h for solvent degreasing, then heating to 400° C. at a rate of 10° C. / min and keeping the temperature for 6 h for thermal degreasing to obtain a degreased embryo;

[0155] (6) Sinter the degreased embryo obtained in step (5) at 1150° C. for 6 h in an air atmosphere to obtain a ferrite tile.

[0156] Example 5

[0157] The present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising:

[0158] (1) mixing an additive having an average particle size of 2 μm into a coarse permanent ferrite powder having an average particle size of 5 μm, and then wet-milling the mixture, and drying the mixture to obtain a ferrite powder having an average particle size of 1 μm;

[0159] The chemical formula of the permanent ferrite coarse powder includes Sr 0.20 Ca 0.28 La 0.52 Fe 11.4 Co 0.30 O 19 , the additives are SiO2, CaCO3, H3BO3, ZnO and Al2O3, based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.6wt%, the mass fraction of CaCO3 is 1.3wt%, the mass fraction of H3BO3 is 0.3wt%, the mass fraction of ZnO is 0.2wt% and the mass fraction of Al2O3 is 0.4wt%;

[0160] (2) taking the ferrite powder obtained in step (1), heating it to 120° C. while stirring, then adding 15% citric acid, and continuing to stir for 5 minutes to obtain a first mixed powder; heating the first mixed powder to 130° C. while stirring, then adding butyl stearate, and continuing to stir for 20 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 100° C., then adding polyamide wax and a binder, and continuing to mix for 20 minutes to obtain a final mixed material;

[0161] Based on the mass of the mixed material, the mass fraction of the ferrite magnetic powder is 91wt%, the mass fraction of 15% citric acid is 0.8wt%, the mass fraction of butyl stearate is 0.4wt%, the mass fraction of the binder is 7.3wt%, and the mass fraction of the polyamide wax is 0.5wt%;

[0162] Taking the mass of the binder as 100%, the mass fraction of paraffin in the binder is 60wt%, the mass fraction of stearic acid wax is 15wt%, the mass fraction of high-density polyethylene is 10wt%, and the mass fraction of low-density polyethylene is 10wt%;

[0163] (3) kneading the mixture obtained in step (2) at 150° C. for 1 h, and granulating to obtain permanent magnet ferrite particles with an average particle size of 6 mm;

[0164] (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 150° C. and a pressure of 75 bar, and obtaining an embryo after natural cooling;

[0165] (5) Soaking the embryo body obtained in step (4) in kerosene at a temperature of 60° C. for 5 h for solvent degreasing, then heating to 800° C. at a rate of 15° C. / min and keeping the temperature for 4 h for thermal degreasing to obtain a degreased embryo body;

[0166] (6) Sinter the degreased embryo obtained in step (5) at 1200° C. for 4 h in an air atmosphere to obtain a ferrite tile.

[0167] Example 6

[0168] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that the injection molding temperature in step (4) is 80°C.

[0169] Example 7

[0170] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that the injection molding temperature in step (4) is 180°C.

[0171] Example 8

[0172] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that step (5) of immersing the embryo obtained in step (4) in kerosene at a temperature of 50° C. for 8 hours for solvent degreasing is omitted.

[0173] Example 9

[0174] The present invention provides a method for preparing ferrite magnetic tiles, which is the same as Example 1 except that the step (5) of heating to 700°C at a rate of 12°C / min. and then keeping the temperature for 6 hours for thermal degreasing is replaced by directly keeping the temperature at 400-800°C for 4-6 hours for thermal degreasing without performing a heating process.

[0175] Comparative Example 1

[0176] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that the sintering temperature in step (6) is 1050°C.

[0177] Comparative Example 2

[0178] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that the sintering temperature in step (6) is 1300°C.

[0179] Comparative Example 3

[0180] The present invention provides a method for preparing a ferrite magnetic tile, which is the same as that of Example 1 except that step (5) and step (6) are omitted.

[0181] Comparative Example 4

[0182] The present invention provides a method for preparing a ferrite magnetic tile, the preparation method comprising: mixing a mixture of a permanent ferrite coarse powder with an average particle size of 0.8 to 1.2 μm and a ball milling additive, and molding, sintering, and grinding in a magnetic field to obtain a ferrite magnetic tile with the same size and specification as that of Example 1;

[0183] The permanent ferrite coarse powder is Sr 0.15 Ca 0.35 La 0.50 Fe 11.4 Co 0.26 O 19 The ball milling additive is a mixture of SiO2, CaCO3, H3BO3 and Cr2O3, wherein the mass fraction of SiO2 in the mixture is 0.4wt%, the mass fraction of CaCO3 is 1.8wt%, the mass fraction of H3BO3 is 0.5wt%, and the mass fraction of Cr2O3 is 0.4wt%.

[0184] The central surface magnetism, magnetic energy product, density, compressive strength, yield rate and material utilization rate of the ferrite magnetic tiles in Examples 1 to 9 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1;

[0185] The center surface magnetism test method is as follows: the center surface magnetism of the magnetic tile refers to the surface magnetic flux intensity at the center position of the inner arc of the finished magnetic tile tested by a general gauss meter;

[0186] The testing method of the magnetic energy product is as follows: the magnetic energy product of the magnetic tile is obtained by grinding a square sample at the middle position of the magnetic tile, and the magnetic energy product of the material is obtained by testing the magnet demagnetization curve using a BH comprehensive tester;

[0187] The density test method is as follows: the density of the magnetic tile is tested by using a kerosene densitometer using a water displacement method to test the density of the magnet;

[0188] The compressive strength test method is as follows: the compressive strength of the magnetic tile is tested by a universal testing machine on the finished magnetic tile;

[0189] The test method of the yield rate is as follows: the yield rate of magnetic tile products refers to the number of qualified products in a batch divided by the total number of batch products multiplied by 100%;

[0190] The testing method of the material utilization rate is as follows: the material utilization rate of the magnetic tile product refers to the mass of the finished magnetic tile divided by the mass of the corresponding magnetic powder in the formed blank magnetic tile multiplied by 100%.

[0191] Table 1

[0192]

[0193]

[0194] From Table 1, we can get:

[0195] (1) The ferrite magnetic tiles prepared in Examples 1 to 5 exhibit excellent magnetic properties, with a central surface magnetism of 630 to 700 Gs, a magnetic energy product of 4.5 to 5.2 MGOe, and a density of 4.8 to 5.2 g / cm 3 , compressive strength is 480~680N;

[0196] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the temperature of injection molding in step (4) of the present invention will affect the performance and strength of the ferrite magnetic tile; when the temperature of injection molding is low, it will lead to poor fluidity of the magnetic powder, poor orientation during injection molding, insufficient molding of the prepared ferrite magnetic tile, and poor surface quality, which will lead to poor performance of the prepared ferrite magnetic tile and decreased compressive strength; when the temperature of injection molding is high, it will cause thermal decomposition of the binder part, and it is also easy to cause thermal damage and burning, thereby affecting the performance and compressive strength of the ferrite magnetic tile obtained by injection molding;

[0197] (3) By comparing Example 1 with Example 8, it can be seen that the solvent degreasing in the present invention affects the performance of the ferrite magnetic tile. This is because in the present invention, most of the paraffin is removed by long-term immersion in kerosene, which avoids the volatilization of paraffin during sintering and causes excessive and uneven pores, thereby improving the strength of the product. The obtained product has uniform pores and high density, and the density of the embryo after degreasing is high, and the overall material utilization rate and yield rate are improved;

[0198] (4) By comparing Example 1 with Example 9, it can be seen that the heating process in the thermal degreasing step of the present invention will affect the performance of the ferrite magnetic tile; when the heating process in the thermal degreasing step is omitted and the heat preservation treatment is directly performed, the performance of the ferrite magnetic tile will be reduced. This is because in the thermal degreasing step of the present invention, by adopting a process of slowly heating from a low temperature, the organic binder other than the paraffin is slowly melted and gradually seeps out of the surface of the embryo obtained by injection molding, thereby avoiding the gasification of these organic substances in the subsequent sintering process and generating a large number of irregular pores, thereby improving the strength of the finished product and ensuring the density of the product, thereby finally obtaining a high-density ferrite magnetic tile;

[0199] (5) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the sintering temperature in step (6) of the present invention will affect the performance of the ferrite magnetic tile; when the sintering temperature is low, the performance of the ferrite magnetic tile will be reduced. This is because when the sintering temperature is low, the structure of the prepared ferrite magnetic tile is not firm, the size is unstable and the surface quality is poor; when the sintering temperature is high, the performance of the ferrite magnetic tile will be reduced. This is because when the sintering temperature is high, the prepared ferrite magnetic tile will be thermally deformed, and it is difficult to obtain a ferrite magnetic tile that meets the size requirements. It will also cause the surface to melt or burn, and produce bubbles, holes or burn marks and other surface quality problems;

[0200] (6) By comparing Example 1 with Comparative Example 3, it can be seen that step (5) and step (6) in the preparation method of the present invention will affect the performance of the ferrite magnetic tile; in the present invention, most of the paraffin is firstly removed by long-term immersion in kerosene, thereby avoiding the volatilization of paraffin during sintering to cause excessive and uneven pores, thereby improving the strength of the product, and the obtained product has uniform pores and high density, and the density of the embryo after degreasing is high; then in the hot degreasing step, by adopting a process of slowly heating from low temperature, the organic binder other than the paraffin is slowly melted and gradually seeps out of the surface of the embryo obtained by injection molding, thereby avoiding the gasification of these organic substances during the subsequent sintering process to produce a large number of irregular pores, thereby improving the strength of the finished product and ensuring the density of the product, thereby finally obtaining a high-density ferrite magnetic tile;

[0201] (7) By comparing Example 1 with Comparative Example 4, it can be seen that the performance of the ferrite magnetic tile obtained by the preparation method of the present invention is significantly higher than that of the existing injection-molded permanent ferrite magnet.

[0202] In summary, the ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention exhibits excellent magnetic properties, with a central surface magnetism of 630-700Gs, a magnetic energy product of 4.5-5.2MGOe, and a density of 4.8-5.2g / cm 3 The compressive strength is 480-680N, which is significantly higher than that of the existing injection molded permanent ferrite magnets. The ultra-thin magnetic tile with a large curvature obtained by the preparation method of the present invention has fewer internal dark cracks and basically does not require subsequent grinding processing, which not only reduces the risk of stress damage during processing, but also improves the yield and utilization rate of the material. The yield rate is not less than 95%, and the material utilization rate is not less than 90%, thereby reducing the production cost and meeting the requirements of mass production.

[0203] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a ferrite magnetic tile, characterized in that: The preparation method comprises: The mixture of ferrite magnetic powder and binder is injection molded and then sintered to obtain ferrite magnetic tiles; The sintering temperature is 1150-1240°C.

2. The preparation method according to claim 1, characterized in that: The mixed material also includes a surface modifier, a coupling agent and a flow aid; Preferably, based on the mass of the mixed material, the mass fraction of the ferrite powder is 88.3-94.3wt%, the mass fraction of the surface modifier is 0.1-0.9wt%, the mass fraction of the coupling agent is 0.3-1.0wt%, the mass fraction of the binder is 5-9wt%, and the mass fraction of the flow aid is 0.3-0.8wt%; Preferably, the surface modifier includes any one of phosphoric acid, oxalic acid, acetic acid, and citric acid, or a combination of at least two thereof; Preferably, the concentration of the surface modifier is 10 to 20 wt %; Preferably, the coupling agent comprises stearic acid and / or an ester derivative of stearic acid; Preferably, the ester derivatives of stearic acid include butyl stearate and / or octyl stearate; Preferably, the flow aid comprises polyamide wax; Preferably, the binder comprises: paraffin wax and / or microcrystalline wax, stearic acid wax, high-density polyethylene and low-density polyethylene; Preferably, based on the mass of the binder, the mass fraction of paraffin wax and / or microcrystalline wax is 50-70wt%, the mass fraction of stearic acid wax is 10-20wt%, the mass fraction of high-density polyethylene is 10-15wt%, and the mass fraction of low-density polyethylene is 10-15wt%; Preferably, the method for preparing the mixed material comprises: mixing ferrite magnetic powder, a surface modifier, a coupling agent and a binder to obtain a mixed material; Preferably, the mixing comprises: mixing the ferrite magnetic powder and the surface modifier at a first temperature to obtain a first mixed powder, then adding a coupling agent and mixing at a second temperature to obtain a second mixed powder, and further adding a flow aid and a binder and mixing at a third temperature to obtain a mixed material; Preferably, the first heating and mixing comprises: taking ferrite magnetic powder, heating it to 80-120° C. while stirring, then adding a surface modifier, and continuing to stir for 5-15 minutes to obtain a first mixed powder; Preferably, the second temperature-raising mixing comprises: heating the first mixed powder to 90-130° C. while stirring, then adding a coupling agent, and continuing stirring for 20-40 minutes to obtain a second mixed powder; Preferably, the third heating and mixing method includes: adjusting the temperature of the second mixed powder to 80-100° C., then adding a flow aid and a binder, and continuing to mix for 20-40 minutes to obtain a final mixed material; Preferably, the moisture content of the first mixed powder is not higher than 600 ppm; Preferably, the moisture content of the second mixed powder is not higher than 900 ppm.

3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the ferrite magnetic powder comprises: mixing an additive into a permanent ferrite coarse powder with an average particle size of 4 to 6 μm, and then wet ball milling the mixture, and drying the mixture to obtain a ferrite magnetic powder with an average particle size of 0.8 to 1.2 μm; Preferably, the chemical formula of the permanent ferrite coarse powder includes A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or any one or a combination of at least two of Sr and Ba, 0.25≤x≤0.45, 0.35≤y≤0.55, 0.25≤z≤0.40, 0.6≤z / y≤0.9 and 5.1≤n≤5.6; Preferably, the additives include SiO2, CaCO3 and H3BO3; Preferably, the additive further comprises Al2O3, Cr2O3, ZnO and SrCO3; Preferably, the average particle size of the additive is not greater than 5 μm; Preferably, based on the total mass of the permanent magnet ferrite coarse powder and the additives, the mass fraction of SiO2 is 0.05-2.0wt%, the mass fraction of CaCO3 is 0.4-2.0wt%, the mass fraction of Al2O3 is 0-2.0wt%, the mass fraction of Cr2O3 is 0-1.5wt%, the mass fraction of ZnO is 0.1-0.6wt%, the mass fraction of SrCO3 is 0.1-1.0wt%, and the mass fraction of H3BO3 is 0.1-0.8wt%.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The preparation method further comprises mixing and granulation performed in sequence before the injection molding; Preferably, the mixing temperature is 100-150°C and the mixing time is 1-3h; Preferably, the average particle size of the mixed material obtained after the granulation is 6 to 8 mm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The injection molding temperature is 100-150°C; Preferably, the injection molding pressure is 75 to 200 bar; Preferably, the injection molding is performed in a tile-shaped molding cavity with a magnetic field; Preferably, natural cooling is further included between the injection molding and the sintering.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method further comprises degreasing between the injection molding and the sintering; Preferably, the degreasing comprises solvent degreasing and thermal degreasing performed sequentially; Preferably, the solvent degreasing comprises: soaking the embryo body obtained by injection molding in kerosene; Preferably, the soaking temperature is 40-60°C and the soaking time is 5-8h; Preferably, the thermal degreasing comprises sequentially heating and heat preservation; Preferably, the heating rate is 10-15°C / min, and the terminal temperature is 400-800°C; Preferably, the insulation time is 4 to 6 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The sintering time is 2 to 6 hours; The sintering is performed in an air atmosphere.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) Additives having an average particle size of no more than 5 μm are mixed into coarse permanent ferrite powder having an average particle size of 4 to 6 μm, and then wet-milled to obtain ferrite powder having an average particle size of 0.8 to 1.2 μm after drying; The chemical formula of the permanent ferrite coarse powder includes A 1-x-y Ca x La y Fe 2n-z Co z O 19 , wherein A includes Sr or any one or a combination of at least two of Sr and Ba, 0.25≤x≤0.45, 0.35≤y≤0.55, 0.25≤z≤0.40, 0.6≤z / y≤0.9 and 5.1≤n≤5.6; Taking the total mass of the permanent magnet ferrite coarse powder and the additive as 100%, the mass fraction of SiO2 is 0.05-2.0wt%, the mass fraction of CaCO3 is 0.4-2.0wt%, the mass fraction of Al2O3 is 0-2.0wt%, the mass fraction of Cr2O3 is 0-1.5wt%, the mass fraction of ZnO is 0-0.6wt%, the mass fraction of SrCO3 is 0.1-1.0wt%, and the mass fraction of H3BO3 is 0-0.8wt%; (2) taking the ferrite powder obtained in step (1), heating it to 80-120° C. while stirring, then adding a surface modifier, and continuing to stir for 5-15 minutes to obtain a first mixed powder; heating the first mixed powder to 90-130° C. while stirring, then adding a coupling agent, and continuing to stir for 20-40 minutes to obtain a second mixed powder; adjusting the temperature of the second mixed powder to 80-100° C., then adding a flow aid and a binder, and continuing to mix for 20-40 minutes to obtain a final mixed material; Based on the mass of the mixed material, the mass fraction of the ferrite powder is 88.3-94.3wt%, the mass fraction of the surface modifier is 0.1-0.9wt%, the mass fraction of the coupling agent is 0.3-1.0wt%, the mass fraction of the binder is 5-9wt%, and the mass fraction of the flow aid is 0.3-0.8wt%; Based on the mass of the binder, the mass fraction of paraffin wax and / or microcrystalline wax is 50-70wt%, the mass fraction of stearic acid wax is 10-20wt%, the mass fraction of high-density polyethylene is 10-15wt%, and the mass fraction of low-density polyethylene is 10-15wt%; (3) kneading the mixture obtained in step (2) at 100-150° C. for 1-3 hours, and granulating to obtain permanent magnet ferrite particles with an average particle size of 6-8 mm; (4) injecting the permanent magnet ferrite particles obtained in step (3) into a tile-shaped molding cavity at a temperature of 100 to 150° C. and a pressure of 75 to 200 bar, and obtaining an embryo after natural cooling; (5) soaking the embryo obtained in step (4) in kerosene at a temperature of 40 to 60° C. for 5 to 8 hours for solvent degreasing, then heating to 400 to 800° C. at a rate of 10 to 15° C. / min and keeping the temperature for 4 to 6 hours for thermal degreasing to obtain a degreased embryo; (6) Sintering the degreased embryo obtained in step (5) at 1150-1240° C. for 2-6 hours in an air atmosphere to obtain a ferrite tile.

9. A ferrite magnetic tile, characterized in that: The ferrite magnetic tile is obtained by the preparation method described in any one of claims 1 to 8.

10. The ferrite magnetic tile according to claim 9, characterized in that: The ferrite magnetic tile has an arc greater than 150° and a thickness not greater than 2.0 mm; Preferably, the magnetic energy product of the ferrite magnetic tile is 4.5-5.2 MGOe.

Citation Information

Patent Citations

  • Permanent magnet ferrite material for injection molding and manufacture method thereof

    CN102136332A

  • Manufacture method of permanent magnet ferrite material powder for injection molding

    CN102351525A